2020
DOI: 10.7739/jkafn.2020.27.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Preventive Behavior against Coronavirus Disease 2019 (COVID-19) among Medically Inclined College Students

Abstract: Purpose: Coronavirus Disease 2019 (COVID-19), an emerging infectious disease introduced in South Korea in 2020. Medically inclined college students are more susceptible to be infected by the virus. The purpose of this study was to investigate factors influencing preventive behavior against COVID-19 among medically inclined college students.Methods: This is a cross-sectional study using a questionnaire survey. Data were collected from 400 medically inclined college students from four colleges of medice. Indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
3
17
4
4
Order By: Relevance
“…The total score ranged from 0 to 10 points, with a higher score indicating a more positive attitude toward overcoming the COVID-19 pandemic. The Cronbach's α was 0.82 in the study by Kim et al [17] and 0.77 in this study.…”
Section: Covid-19 Attitudesupporting
confidence: 54%
See 1 more Smart Citation
“…The total score ranged from 0 to 10 points, with a higher score indicating a more positive attitude toward overcoming the COVID-19 pandemic. The Cronbach's α was 0.82 in the study by Kim et al [17] and 0.77 in this study.…”
Section: Covid-19 Attitudesupporting
confidence: 54%
“…COVID-19 knowledge was evaluated using a 15-item tool developed by Taghrir et al [16] for medical students based on the diagnosis and treatment protocol of the National Health Commission of China, and modified and supplemented by Kim et al [17]. The tool consisted of 15 items in total, including five items on public prevention behaviors for COVID-19, two items for infection route, two items for prevention and treatment as a health care professional, four items for etiology and symptoms, and two items for definition and diagnosis.…”
Section: Covid-19 Knowledgementioning
confidence: 99%
“…In previous studies about infectious diseases, including Middle East respiratory syndrome (MERS) [12] and severe acute respiratory syndrome (SARS) [13], the knowledge and attitudes were found to be correlating variables with preventive practice. A few KAP studies on COVID-19 reported similar findings, and most of them were conducted on native college or university students majoring in nursing or medicine [14][15][16], which may be not be generalizable to international students. Moreover, very few studies have explored the relationship between trust in a quarantine system and preventive practice.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, nurses contribute to providing a better working environment by providing emotional support through education to employees who are concerned about being infected with the virus themselves [49]. Therefore, a healthcare education system that can enhance the level of knowledge about COVID-19, actively practice prevention activities [50], and increase patient participation must be implemented [44].…”
Section: Discussionmentioning
confidence: 99%